Acculturing of Islamic Values in The Nyangku Panjalu Ciamis Tradition - Nur Shofiah, Aji (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
This study examines the Islamic values ​​contained in the Nyangku ceremony in the midst of the existence of the Islamic values ​​of the Panjalu community. The Panjalu community is known for its Islam which is thick with the practice of local traditions in this case is Nahdlatul Ulama (NU). In addition, this study also wants to know the response of Panjalu Muslims to the Nyangku ceremony. This type of research is a qualitative research with a descriptive analysis approach. Sources of data used in this study is in the form of literature data and data obtained from interviews. Nyangku for the people of Panjalu is a great ritual because it contains certain meanings and values. Apart from having a certain purpose from the Panjalu kingdom itself, the nyangku ceremony is also a means of spreading Islam. The Nyangku ceremony is usually held once a year on the last Monday or Thursday of the month of Rabi'ul Awal. The purpose of the nyangku is to clean the heirlooms of the Panjalu kingdom. The purpose of holding the Nyangku ceremony is to clean up heirlooms from the Panjalu Kingdom. The essence of the nyangku ceremony is to cleanse oneself of everything that is prohibited by Islam. In addition, it also aims to commemorate the birthday of the Prophet Muhammad SAW and as a means of strengthening brotherhood among the Panjalu people. The internalization of Islamic values ​​in the Nyangku ceremony can be seen in the aspect of the celebration date which coincides with the Birthday of the Prophet Muhammad SAW and the purification of heirlooms which has the meaning of cleansing the heart because Islam is a holy religion which also symbolizes tolerance among others.